Urban Landscapes in High-Density Cities Parks, Streetscapes, Ecosystems - Rinaldi, Bianca Maria; Tan, Puay Yok (Birkhäuser, 2019)
The benefits and positive effects of urban green spaces are well-known, ranging from the promotion of health, support of biodiversity to climate regulation. However, the practical implementation of urban landscapes is less discussed. How can we make these spaces functional, economically feasible and inclusive, especially as cities become more culturally diverse? The publication seeks to provide answers to these pressing queries. Its interdisciplinary approach involves the expertise of landscape architects and planners, architects, ecologists and geographers from renowned universities. Urban Landscapes in High-Density Cities analyzes original schemes for challenged neighborhoods and explores strategies to reconcile the various demands, such as food production, resilience and nature conservation. Indeed, urban landscapes have to be restorative, ecological and aesthetically pleasing at the same time. This is a particular challenge in high-density cities like Singapore, Seoul or New York where space is a scare commodity. And the continuing groth of the worldwide urban population imbues the topic with a special urgency.
Keywords: Städtebau; Ökosystem; Ballungsraum; Aufsatzsammlung